Influence of high-temperature condition on the microstructure and properties of FeCoCrNiAl0.3 and FeCoCrNiAl0.7 high-entropy alloy coatings. (1st February 2021) - Cai, Yangchuan; Zhu, Lisong; Cui, Yan; Geng, Keping; Han, Tengfei; Manladan, Sunusi Marwana; Luo, Zhen; Han, Jian
ABSTRACT: In the present study, FeCoCrNiAl x ( x = 0.3, 0.7) coatings were fabricated by laser cladding technology. XRD analysis and scanning electron microscopy (SEM) were used to investigate the evolution of phases and microstructures before and after the high-temperature oxidation test. The micro-hardness, tribological behaviour, and corrosion resistance of the coatings, before and after the high-temperature treatment, were systematically investigated using micro-hardness test, abrasive wear test, and electrochemical corrosion test. The microstructure and properties of FeCoCrNiAl0.3 cladding layer changed little before and after the high-temperature oxidation test. The high-temperature condition promoted the generation of BCC solid solutions at the grain boundaries when the Al element content was 14.89% (i.e. 0.7 mol). This enhanced the micro-hardness and tribological behaviour, but deteriorated the corrosion resistance.